Ordinary mysticism : your life as sacred ground - Starr, Mirabai (Harper One, an imprint of HarperCollinsPublishers, 2024)
Welcome to the temple of your regular life. So begins beloved spiritual guide Mirabai Starr's stunning exploration of finding the extraordinary in the everyday. In Ordinary Mysticism, she helps readers discover their own inner mystic and let go of the limiting belief that spiritual life exists only in traditional places of worship. Mysticism, she explains, is a direct experience of the sacred--no church or clergy required. Our everyday life can be an encounter with the sacred if we pay attention.--